Vezikulární a pronukleacní glykoproteiny v patogenezi cholesterolové litiázy - Jirsa, M; Smíd, F; Marecek, Z (Casopis lekaru ceskych, 1998)
BACKGROUND: Several biliary proteins have been known to accelerate fusion of cholesterol rich phospholipid vesicles. Some of them are present in vesicular membrane, localisation of other proteins is unknown. Biliary glycoprotein has not been studied in consequence with pathogenesis of cholesterol lithiasis. METHODS AND RESULTS: Low molecular extravesicular proteins were separated from vesicles by gel filtration on a 1200mm column of Sephacryl S-300 HR. Immunoglobulins IgM, IgA, haptoglobin, biliary glycoprotein I (BGP I) and nonspecific crossreactive antigen were eluted along with vesicles. Albumin and alpha 1-acid glycoprotein were eluted later and must be extravesicular. CONCLUSIONS: Fact that BGP I (85 kDa membrane glycoprotein) eluted along with vesicles and not in albumin fraction suggests that it might be bound in vesicular membrane. As a known adhesion molecule it could thus play an important role in pathogenesis of cholesterol cholelithiasis.
Keywords: cholelitiáza; Glycoproteins; glykoproteiny; Cholesterol; techniky in vitro; cholesterol; In Vitro Techniques; Bile; lidé; Cholelithiasis; Chromatography, Gel; Humans; žluč; gelová chromatografie